Sorting it out: Technical barriers to trade and industry productivity - Gabriel J. Felbermayr; Benjamin Jung (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2008)
Trade economists traditionally study the effect of lower variable trade costs. While increasingly important politically, technical barriers to trade (TBTs) have received less attention. Viewing TBTs as fixed regulatory costs related to the entry into export markets, we use a model with heterogeneous firms, trade in differentiated goods, and variable external economies of scale to sort out the rich interactions between TBT reform, input diversity, firm-level productivity, and aggregate productivity. We calibrate the model for 14 industries in order to clarify the theoretical ambiguities. Overall, our results tend to suggest beneficial effects of TBT reform but also reveal interesting sectoral variation.
urn:nbn:de:bsz:21-opus-32484
Keywords: F12; F13; F15; 330; heterogeneous firms; international trade; single European market; technical barriers to trade; regulatory costs; Nichttarifäre Handelshemmnisse; Industriegüteraußenhandel; Verarbeitendes Gewerbe; Außenhandelsliberalisierung; Produktivität; Theorie; EU-Staaten